(untitled) (Bangladesh Journal of Pharmacology, 2017)
The aim of the present study was to analyze the anti-cancer effect of Orthosiphon stamineus leaf extract on MCF-7 cells. Ethyl acetate extract of the plant was eluted and pooled into 6 fractions based on their Rf values and the fractions were tested for cytotoxicity. Fraction 3 was found effective (IC50 = 28.5 µL/mL) and was subjected to LC-MS analysis which indicated the presence of biochanin, eleutherol and cinnamic acid. Further, cytotoxic effect of the fraction was confirmed in terms of nucleolin, bcl2, bax and cytochrome c expression in MCF-7 cells through RT-PCR where a marked decrease in nucleolin, bcl2 and increase in bax and cytochrome c were observed. The presence of eleutherol, a well-known anti-oxidant and anti-cancer agent, has been reported for the first time in O. stamineus. The anti-cancer activity of O. stamineus may be due to the presence of elutherol and cinnamic acid. Video Clip of Methodology: LC-MS analysis of Orthosiphon stamineus extract: 7 min 33 sec Full Screen Alternate